Principles of posterior knee joint instability treatment (literature review) - Golovakha, Maksim; Didenko, Inna; Krasnoperov, Sergiy; Titarchuk, Rostyslav; Benedetto, Кarl; Orljanski, Weniamin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Damage of posterior crucial ligament postern-lateral stabilizing structures is a significant injury to the knee. Incomplete diagnosis of lesions in the acute period of trauma and subsequent inadequate treatment leads to functional instability and rapid progression of degenerative processes. Objective: based on the analysis of scientific literature to identify further direction for improving surgical techniques and improving outcomes of patients with posterior instability of the knee joint. Methods: keyword search on problems of diagnosis, classification and selection method for treating posterior knee instability in the english-speaking academic libraries, databases Pubmed, Medline, Cochrane library and the Russian media over the past 15 years. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Results:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> mechanisms of posterior crucial ligament injury are very diverse. Damage can be isolated or combined, have a chronic course. In recent years, increased interest in the reconstruction of all the internal structures of the knee. Reports of the functional results of posterior crucial ligament surgical treatment is less than anterior crucial ligament. The significance of the problem is associated with low frequency and less surgical treatment of posterior crucial ligament injuries, as well as the heterogeneity of acute, chronic and combined it with the potential damage involving posterolateral joint. Damage of posterior crucial ligament often remains unrecognized and therefore untreated. The authors analyzed the methods used today to treat patients with posterior instability of the knee joint, whereby defined prospects for improving surgical techniques and improving outcomes.